2022
DOI: 10.3390/ijerph19063472
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Families’ Acceptance of Wearable Activity Trackers: A Mixed-Methods Study

Abstract: Background: The family environment plays a crucial role in child physical activity (PA). Wearable activity trackers (wearables) show potential for increasing children’s PA; however, few studies have explored families’ acceptance of wearables. This study investigated the acceptability of using wearables in a family setting, aligning experiences with components of the Technology Acceptance Model and Theoretical Domains Framework. Methods: Twenty-four families, with children aged 5–9 years, took part in a 5-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 87 publications
(144 reference statements)
0
33
0
Order By: Relevance
“…Previous research has similarly found that parental screen use is associated with child screen use, with parental attitudes towards screen use also having an impact (Lauricella et al 2015). A recent study found that providing parents and children with a wearable can increase awareness of PA levels and promote PA via competition (Creaser et al 2022), with another study finding wearables can prompt families to discuss health with one another (Sharaievska et al 2019). Therefore, parent wearable use (current or previous) impacts child/adolescent wearable use, and this co-use of wearables may be beneficial, such as adopting healthier lifestyles (Creaser et al 2022) and increasing conversations about health (Sharaievska et al 2019).…”
Section: Opportunitymentioning
confidence: 95%
See 4 more Smart Citations
“…Previous research has similarly found that parental screen use is associated with child screen use, with parental attitudes towards screen use also having an impact (Lauricella et al 2015). A recent study found that providing parents and children with a wearable can increase awareness of PA levels and promote PA via competition (Creaser et al 2022), with another study finding wearables can prompt families to discuss health with one another (Sharaievska et al 2019). Therefore, parent wearable use (current or previous) impacts child/adolescent wearable use, and this co-use of wearables may be beneficial, such as adopting healthier lifestyles (Creaser et al 2022) and increasing conversations about health (Sharaievska et al 2019).…”
Section: Opportunitymentioning
confidence: 95%
“…The survey consisted of between 19 and 23 items (including demographic questions), depending on whether the child; (1) currently (n = 21), (2) previously (but no longer) (n = 23), or (3) had never (n = 19) used a wearable. Questions were developed based on previous research using the same theoretical underpinnings (TDF, COM-B model) (Creaser et al 2022;Eddy et al 2021), and were derived based on the recommendations and terminology outlined by Michie et al (2015) (e.g. using examples from the 'COM-B self-evaluation questionnaire'; Michie et al 2015) The face validity of the survey items was evaluated by a multi-disciplinary team (n = 5), who provided critical insights into the appropriateness of the items, compared to the definitions outlined by Michie et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations